Peran Bimbingan Baca Al-Qur’an dalam Pembinaan Moral Anak di Madrasah Diniyah Darussalamah - Ihsanudin Ihsanudin; Dian Tias Aorta (ALSYS, 2026)
Technological development and globalization over the past decade have affected the decline in the quality of social interaction and the increase in children’s individualistic behavior, making the strengthening of morality and social cohesion through religious education increasingly important. This study aims to describe the role of Al-Qur’an reading guidance in moral development and its contribution to the formation of children’s social cohesion at Madrasah Diniyah Darussalamah. This study employed a qualitative approach with a case study design, involving 15 santri and 1 ustadz selected purposively. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Al-Qur’an reading guidance conducted regularly was able to foster discipline, responsibility, and patience among the santri. In addition, this activity also encouraged the formation of positive social interactions, such as mutual respect, waiting for one’s turn, and complying with shared rules. A structured learning pattern and direct interaction between the ustadz and the santri became important factors in the process of internalizing moral and social values. These findings affirm that Al-Qur’an reading guidance functions not only as cognitive learning, but also as an effective means of moral development and strengthening children’s social cohesion, while also providing practical implications for the development of value-based learning that integrates cognitive, affective, and social aspects in religious education.